The state of the science on the health benefits of blueberries: a perspective - Stull, April J.; Cassidy, Aedín; Djousse, Luc; Johnson, Sarah A.; Krikorian, Robert; Lampe, Johanna W.; Mukamal, Kenneth J.; Nieman, David C.; Porter Starr, Kathryn N.; Rasmussen, Heather; Rimm, Eric B.; Stote, Kim S.; et al. (Frontiers in Nutrition, 2024)
Mounting evidence indicates that blueberry consumption is associated with a variety of health benefits. It has been suggested that regular consumption of blueberries can support cardiovascular disease and function, pre-diabetes and type 2 diabetes, and brain and cognitive function in individuals with health conditions and age-related decline. Further, mechanistic investigations highlight the role of blueberry anthocyanins in mediating these health benefits, in part through interactions with gut microbiota. Also, nutritional interventions with blueberries have demonstrated the ability to improve recovery following exercise-induced muscle damage, attributable to anti-inflammatory effects. Despite these advancements in blueberry health research, research gaps persist which affects the generalizability of findings from clinical trials. To evaluate the current state of knowledge and research gaps, a blueberry health roundtable with scientific experts convened in Washington, DC (December 6-7, 2022). Discussions centered around five research domains: cardiovascular health, pre-diabetes and diabetes, brain health and cognitive function, gut health, and exercise recovery. This article synthesizes the outcomes of a blueberry research roundtable discussion among researchers in these domains, offering insights into the health benefits of blueberries and delineating research gaps and future research directions.